Modeling risks in marine protected areas: Mapping of habitats, biodiversity, and cultural ecosystem services in the southernmost atlantic coral reef - Niz, Willians C.; Laurino, Ivan R.A.; Freitas, Débora M. de [UNESP]; Rolim, Fernanda A.; Motta, Fabio S.; Pereira-Filho, Guilherme H. (My University, 2023)
Marine Protected Area (MPA) is a fundamental strategy for the maintenance of ocean ecological processes worldwide and, consequently, their associated ecosystem services. Nevertheless, the quality of the services provided by MPAs, including cultural services such as recreational activities, depends on the effective management of marine habitats and biodiversity. Here, we performed an ecosystemic assessment in reef environments within a subtropical MPA, modeling the potential risks for their habitats and their recreational activities. The Queimada Grande Island (QGI), southeastern Brazil, was used as the model area since this island encompasses a unique and irreplaceable marine habitat, the Southernmost Atlantic coral reef. We firstly assessed and mapped the habitats, the biodiversity, and the recreational activities associated with QGI reefs. Next, we considered different scenarios of management for the modeling risks across the study area. We found that the coral reef and its adjacent habitats, such as the rhodolith bed, make the sheltered face of the island an important area for the provision of the cultural ecosystem services and overlapping uses such as onboard recreational fishing, spearfishing, and recreational diving. This area was also evaluated as the one under the highest risk of impact, considering the current scenario of management. The most successful scenario modeling to reduce these risks was the hypothetical implementation of a 66% reduction of all activities over all QGI habitats. Despite that, the scenario simulating the application of the regulations present in the MPA management plan was enough to reduce almost half the maximum risk value. Therefore, we concluded that to provide a balance among conservation, uses, and the local economy, the application of these regulations is the better management scenario modeled for the study area. Such results provided useful information and tools for local management and decision-making in this singular marine environment, also being an example for mapping ecosystem services and modeling risks in MPAs worldwide.
Keywords: Fisheries management; Marine protected areas; Marine Spatial Planning; Multiple-use protected areas; Socioecological system